PENGALAMAN KEBERMAKNAAN BELAJAR DALAM PERSPEKTIF FENOMENOLOGI PENDIDIKAN DI STKIP PESISIR SELATAN - Handayani, Revi; Zen, Zelhendri; Jasrial, Jasrial; Sari, Filma Alia; Sefrinal, Sefrinal (STKIP Pesisir Selatan, 2025)
This sociocultural reality cannot be separated from the learning process, as it shapes students' perspectives, motivations, and learning needs. Learning processes that ignore local realities tend to lose relevance, resulting in a disconnect between the theory they learn and their daily lives. This study aims to understand the meaningful learning experiences of students at STKIP Pesisir Selatan through the perspective of educational phenomenology. The focus lies on how students interpret their learning experiences inside and outside the classroom, as well as the factors that shape meaning in the learning process. The phenomenological approach explores students’ subjective experiences in depth. The findings show that meaningful learning depends not only on course material but also on connections to the local cultural context, social support, the lecturer’s role as a facilitator, and students’ intrinsic motivation. This article contributes to the development of more humanistic, contextual, and reflective learning practices in teacher education institutions.